Are perceived stress, depressive symptoms and religiosity associated with alcohol consumption? A survey of freshmen university students across five European countries - Sebena Rene; El Ansari Walid; Stock Christiane; Orosova Olga; Mikolajczyk Rafael T (BMC, 2012)
Abstract Background The aim of this study was to investigate the association of perceived stress, depressive symptoms and religiosity with frequent alcohol consumption and problem drinking among freshmen university students from five European countries. Methods 2529 university freshmen (mean age 20.37, 64.9% females) from Germany (n = 654), Poland (n = 561), Bulgaria (n = 688), the UK (n = 311) and Slovakia (n = 315) completed a questionnaire containing the modified Beck Depression Inventory for measuring depressive symptoms, the Cohen's perceived stress scale for measuring perceived stress, the CAGE-questionnaire for measuring problem drinking and questions concerning frequency of alcohol use and the personal importance of religious faith. Results Neither perceived stress nor depressive symptoms were associated with a high frequency of drinking (several times per week), but were associated with problem drinking. Religiosity (personal importance of faith) was associated with a lower risk for both alcohol-related variables among females. There were also country differences in the relationship between perceived stress and problem drinking. Conclusion The association between perceived stress and depressive symptoms on the one side and problem drinking on the other demonstrates the importance of intervention programs to improve the coping with stress.